Visualization of cardiac uptake of bone marrow mesenchymal stem cell‐derived extracellular vesicles after intramyocardial or intravenous injection in murine myocardial infarction - Cynthia M. Xu; Sharif A. Sabe; Rayane Brinck‐Teixeira; Mohamed Sabra; Frank W. Sellke; M. Ruhul Abid (Physiological Reports, 2023)
Abstract In animal models, human bone marrow mesenchymal stem cell‐derived extracellular vesicles (MSC‐EV) have been found to have beneficial effects in cardiovascular disease, but only when administered via intramyocardial injection. The biodistribution of either intravenous or intramyocardial injection of MSC‐EV in the presence of myocardial injury is uncharacterized at this time. We hypothesized that intramyocardial injection will ensure delivery of MSC‐EV to the ischemic myocardium, while intravenous injection will not. Human bone marrow mesenchymal stem cells were cultured and the MSC‐EV were isolated and characterized. The MSC‐EVs were then labeled with DiD lipid dye. FVB mice with normal cardiac function underwent left coronary artery ligation followed by either peri‐infarct intramyocardial or tail vein injection of 3*106 or 2*109 particles of DiD‐labeled MSC‐EV or a DiD‐saline control. The heart, lungs, liver, spleen and kidneys were harvested 2 h post‐injection and were submitted for fluorescent molecular tomography imaging. Myocardial uptake of MSC‐EV was only visualized after intramyocardial injection of 2*109 MSC‐EV particles (p = 0.01) compared to control, and there were no differences in cardiac fluorescence after tail vein injection of MSC‐EV (p = 0.5). There was no significantly detectable MSC‐EV uptake in other organs after intramyocardial injection. After tail vein injection of 2*109 particles of MSC‐EV, the liver (p = 0.02) and spleen (p = 0.04) appeared to have diffuse MSC‐EV uptake compared to controls. Even in the presence of myocardial injury, only intramyocardial but not intravenous administration resulted in detectable levels of MSC‐EV in the ischemic myocardium. This study confirms the role for intramyocardial injection in maximal and effective delivery of MSC‐EV. Our ongoing studies aimed at developing bioengineered MSC‐EV for targeted delivery to the heart may render MSC‐EV clinically applicable for cardiovascular disease.